Business plan of rental apartments - Pashkina, Valeriia (2018)
The aim of this bachelor thesis is to create a business growth plan for a property management company ‘Vista Riverside’ on how to develop a profitable rent strategy for its existing and new apartment. Theoretical part gives an insight into business planning, with emphasis of marketing strategy and financial plan. It also explains purpose of investment in real estate. Practical part is about implementing theory in practice. It provides information about the company, analysis of the market, marketing strategy and financial forecast.